2021
DOI: 10.3390/v13030370
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Investigation of Batai Virus Infections in Ruminants from the State of Saxony-Anhalt, Germany, 2018

Abstract: Arthropod-borne Batai virus (BATV) is an Orthobunyavirus widely distributed throughout European livestock and has, in the past, been linked to febrile diseases in humans. In Germany, BATV was found in mosquitoes and in one captive harbor seal, and antibodies were recently detected in various ruminant species. We have, therefore, conducted a follow-up study in ruminants from Saxony-Anhalt, the most affected region in Eastern Germany. A total of 325 blood samples from apparently healthy sheep, goats, and cattle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The presence of BATV antibodies has been studied in Eastern Germany across various livestock species including sheep, goat and cattle [ 17 , 18 , 35 ]. These studies have revealed seroprevalences as high as 44.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of BATV antibodies has been studied in Eastern Germany across various livestock species including sheep, goat and cattle [ 17 , 18 , 35 ]. These studies have revealed seroprevalences as high as 44.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance studies conducted in Germany and Italy have confirmed the presence of antibodies against BATV in cattle, sheep and goats. Overall, these studies have demonstrated a seroprevalence up to 44% [ 17 , 18 ]. However, in Europe, BATV-associated disease has not yet been reported in ruminants or humans.…”
Section: Introductionmentioning
confidence: 99%
“…To date no neurological component to the disease has been described in humans, although encephalitis was reported recently in an infected harbor seal [8]. BATV is found throughout Europe and Asia with variable rates of seroprevalence in humans (from <1-32%), that can also remain low despite high rates of infection in livestock in these same regions [2,[9][10][11]. Surprisingly, Bunyamwera serogroup viruses have also shown the ability to dramatically increase their pathogenicity through reassortment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surveillance for anti-Batai virus neutralising antibodies in cattle sampled between 2011 and 2012 in Germany indicated a seroprevalence level of 0.55% [11]. However, more recent studies from Germany have identi ed seroprevalence levels of 36.4% [12] and 41.4% [13], suggesting either an underestimation of seroprevalence in 2011-2012 or that BATV has recently emerged in these areas and can be considered an epizootic in northern Europe. The identi cation of cattle as a key reservoir species is further corroborated by the isolation of BATV from cattle sera sampled from Inner Mongolia, China [14].…”
Section: Introductionmentioning
confidence: 99%